2018
DOI: 10.3389/fnmol.2018.00318
|View full text |Cite
|
Sign up to set email alerts
|

Studying Huntington’s Disease in Yeast: From Mechanisms to Pharmacological Approaches

Abstract: Huntington’s disease (HD) is a neurodegenerative disorder that leads to progressive neuronal loss, provoking impaired motor control, cognitive decline, and dementia. So far, HD remains incurable, and available drugs are effective only for symptomatic management. HD is caused by a mutant form of the huntingtin protein, which harbors an elongated polyglutamine domain and is highly prone to aggregation. However, many aspects underlying the cytotoxicity of mutant huntingtin (mHTT) remain elusive, hindering the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 253 publications
(365 reference statements)
0
21
0
Order By: Relevance
“…The budding yeast post-mitotic cell ageing usually undergoes for 1–2 months of survival and has been widely used in ageing research [26,35,36,37,38,39,40,41,42]. It is believed that evolutionarily conserved key molecules in the polarization processes from yeast budding and mating to metazoan neuronal outgrowth and spinogenesis are homologous, potentially making the yeast chronological ageing process as a useful model for the non-dividing human cell ageing research [43,44,45,46,47,48,49].…”
Section: Cell Chronological Ageingmentioning
confidence: 99%
“…The budding yeast post-mitotic cell ageing usually undergoes for 1–2 months of survival and has been widely used in ageing research [26,35,36,37,38,39,40,41,42]. It is believed that evolutionarily conserved key molecules in the polarization processes from yeast budding and mating to metazoan neuronal outgrowth and spinogenesis are homologous, potentially making the yeast chronological ageing process as a useful model for the non-dividing human cell ageing research [43,44,45,46,47,48,49].…”
Section: Cell Chronological Ageingmentioning
confidence: 99%
“…Since the establishment of the first HD model in yeast (Krobitsch and Lindquist, 2000), several additional yeast HD models have been described, employing the exogenous expression of poly-Q repeats at variable lengths under the control of different promoters (Hofer et al, 2018). In many cases, expression of the longer glutamine expansions, above a threshold not precisely defined in yeast, resulted in cytotoxicity (Solans et al, 2006; Kaiser et al, 2013; Papsdorf et al, 2015; Ruetenik et al, 2016).…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%
“…This study demonstrated the formation of multiple types of aggregates, highly diverse in size and structure. This diversity indicates a complex set of molecular mechanisms underlying cell toxicity, currently hindering their full elucidation (Xi et al, 2016; Hofer et al, 2018). Interestingly, these analyses identified mid-sized aggregates to be associated with cell toxicity in yeast (Xi et al, 2016), in accordance with concurrent findings in mouse neuroblastoma cells (Kim et al, 2016), though in mammalian systems this issue is still under debate (Drombosky et al, 2018).…”
Section: Huntington's Disease (Hd)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has helped in the elucidation of mechanistic features of mHTT cytotoxicity and has established the potential of yeast as a platform for screening for pharmacological agents against HD (ref. 28 ).…”
Section: Yeast As a Model Of Agingmentioning
confidence: 99%